Pemanfaatan Metode Cooperative Script dalam Meningkatkan Kemampuan Membaca Puisi pada Siswa Sekolah Dasar - Kilikily , Cristianti Costafina; Johansz, Dovila (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research aims to investigate the use of the Cooperative Script Method in improving the ability to read poetry in elementary school students. This research was carried out on Class V students of Yamluli Christian Elementary School, Southwest Maluku Regency. This researcher is conducting classroom action research to describe student activities in the Indonesian language learning process using the Cooperative script method to improve poetry reading skills. The results of this research show an increase in poetry reading skills seen in the initial test results with a score of 46.27 and an increase in cycle I with an average score of 63.81 and an increase in cycle II to 72.27 so this research is said to be successful because it has met the KKM. at Yamluli Christian Elementary School it was 65.